Nitric Oxide Signaling in the Auditory Pathway - Kopp-Scheinpflug, Conny; Forsythe, Ian D. (Frontiers in Neural Circuits, 2021)
Nitric Oxide (NO) is of fundamental importance in regulating immune, cardiovascular, reproductive, neuromuscular and nervous system function. It is rapidly synthesized and cannot be confined, it is highly reactive, so its lifetime is measured in seconds. These distinctive properties (contrasting with classical neurotransmitters and neuromodulators) give rise to the concept of NO as a ‘volume transmitter’, where it is generated from an active source, diffuses to interact with proteins and receptors within a sphere of influence or volume, but limited in distance and time by its short half-life. In the auditory system, the neuronal NO-synthetizing enzyme, nNOS, is highly expressed and tightly coupled to postsynaptic calcium influx at excitatory synapses. This provides a powerful activity-dependent control of postsynaptic intrinsic excitability via cGMP generation, PKG activation and modulation of voltage-gated conductances. NO may also regulate vesicle mobility via retrograde signalling. This Mini Review focusses on the auditory system, but highlights general mechanisms by which NO mediates neuronal intrinsic plasticity and synaptic transmission. The dependence of NO generation on synaptic and sound-evoked activity has important local modulatory actions and NO serves as a ‘volume transmitter’ in the auditory brainstem. It also has potentially destructive consequences during intense activity or on spill-over from other NO sources during pathological conditions, when aberrant signalling undermines the precisely timed and tonotopically organized auditory system.